Are the carotid kinking and coiling underestimated entities? - Radak Đorđe; Babić Srđan; Tanasković Slobodan; Matić Predrag; Sotirović Vuk; Stevanović Predrag; Jovanović Predrag; Gajin Predrag (Vojnosanitetski Pregled)
nema